Microwave Assisted Synthesis and Antimicrobial Study of Some Novel 2-Azetidinones Derived from 2-(1-Phenylimino-ethyl)-naphthalen-1-ol - Sainath Zangade; Avinash Shinde; Yogesh Nalwar; Pravinkumar Patil (Orbital: The Electronic Journal of Chemistry, 2019)
Several substituted 2‐azetidinone derivatives 2a-q have been synthesized from halogenohydroxy substituted imines 1a-q under microwave irradiation technique. The reactions were carried out using 2-methoxyethanol as an efficient reaction media to afford high yield of product. The structures of newly synthesized compounds have been established on the basis of elemental analysis, IR, 1H NMR, 13C NMR, GC-MS and elemental data. Further, all newly synthesized compounds were screened for their in vitro antimicrobial activity. The antifungal and antibacterial effects of the tested compounds are due to their molecular structure and substituent present.DOI: http://dx.doi.org/10.17807/orbital.v11i3.1393